A novel fabrication method for titanium dioxide/activated carbon fiber electrodes and the effects of titanium dioxide on phenol degradation. Issue 3 (September 2016) - Wu, Mengya; Ouyang, Yongjian; Zhao, Kang; Ma, Yimei; Wang, Mei; Liu, Deqi; Su, Yanyu; Jin, Peipei
Graphical abstract: Highlights: TiO2 /ACF was prepared via a novel fabrication method ("bottle- in-a- ship"). The amount of TiO2 influenced ACF adsorption and TiO2 /ACF electro-catalytic oxidation of phenol, respectively. TiO2 /ACF material had a better electrochemical degradation of phenol and excellent stability. Abstract: In this paper, the nano-titanium dioxide/activated carbon fiber (TiO2 /ACF) electrodes are prepared by using ship-in-a-bottle method with Ti(OC4 H9 )4 as a raw material. The amounts of TiO2 immobilized on the activated carbon fiber are 0.14, 0.28 and 0.42 g/g ACF, respectively. The adsorption behavior and electro-catalytic oxidation of phenol with these three kinds of electrodes are investigated. Experimental results show that the maximum adsorption quantities of the phenol decreased by 12.41%, 17.25% and 32.38% respectively with the increase of TiO2, while the adsorption rates decreased by 56.22%, 71.26% and 88.73%, respectively. However, the removal efficiency of phenol and the production rate of hydroxyl radicals (OH) increased with the increase of TiO2 . Compared with sol–gel method, TiO2 /ACF electrode prepared by ship-in-a-bottle method not only exhibit better electro-catalytic activity and stability, but also cheaper. Because the amount of Ti(OC4 H9 )4 used to prepare TiO2 can be reduced by more than 33%. In addition, the nano-TiO2 particles, smaller and more uniform in size, can be immobilized firmly and prepared easily in this method.